Hamaca paraguaya: perda e trabalho de luto no cinema latino-americano contemporâneo - Barbara Xavier Franca (2014)
How does Hamaca Paraguaya (Paz Encina, 2006) impart history? The Paraguayan film presents an old couple laid down in a hammock, complaining about life matters and the absence of their son, who has joined the army and has probably died in the battlefield. The movie can be associated with a number of other Latin American films produced in the 21th century. They also deal with petty, trivial, even insignificant, experiences, that Galo Alfredo Torres (2011) grouped together under the label of daily neo-realism. The major events are suppressed, giving place to the everyday life of ordinary characters in their customary environment, engendering narratives in which virtually nothing happens. Contrary to the tendency of the Latin American cinema from the 1960's and 70's, which adopted an explicitly critical position towards the misery in the Third World, the North-American imperialism, the political corruption, the exploitation of people, and the cultural colonization, the cinema of Torres seems to refrain from these issues. According to Andrea Molfetta (2011), the creative impulse of the former movies has been replaced by films that present mourning characters stuck in the past, living a life that never moves forward. In an attempt to identify this change of attitude, we investigate how Hamaca deals with history, taking the absence of the son as the starting point of the analysis. To that end, we revise Torres concept of daily neo-realism and the traits of Latin-American contemporary cinema presented by Molfetta. We also resort to Italian neo-realism in order to discuss the idea of a cinema of absence. By analyzing the mise-en-scène, the off-screen and the temporality in Hamaca, we propose that this is a movie in state of melancholia.